2017
DOI: 10.1017/s1368980017000866
|View full text |Cite
|
Sign up to set email alerts
|

Warnings as a directive front-of-pack nutrition labelling scheme: comparison with the Guideline Daily Amount and traffic-light systems

Abstract: Results from the present work suggest that warnings have potential as directive FOP nutrition labels to improve consumer ability to identify unhealthful products and highlight advantages compared with the traffic-light system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
92
0
23

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(142 citation statements)
references
References 51 publications
(74 reference statements)
27
92
0
23
Order By: Relevance
“…Taken together, our findings from a large sample of Brazilian packaged foods and beverages, sold in supermarkets in the country that control 70% of the retail market share contribute to the literature by showing the pervasive presence of nutrition and health claims in unhealthy products, even more so among those highly consumed by children and adolescents [2,25,40]. Although FoP labeling in the format of warning signs seems to be effective in nudging consumers to choose healthier products [8,11,14,43], when these signs are accompanied by nutrition claims for the same nutrient for which a warning sign is present in the package, this can undermine the efficacy of FoP labeling [17]. Health and nutrition claims have been associated with purchase behavior [44].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Taken together, our findings from a large sample of Brazilian packaged foods and beverages, sold in supermarkets in the country that control 70% of the retail market share contribute to the literature by showing the pervasive presence of nutrition and health claims in unhealthy products, even more so among those highly consumed by children and adolescents [2,25,40]. Although FoP labeling in the format of warning signs seems to be effective in nudging consumers to choose healthier products [8,11,14,43], when these signs are accompanied by nutrition claims for the same nutrient for which a warning sign is present in the package, this can undermine the efficacy of FoP labeling [17]. Health and nutrition claims have been associated with purchase behavior [44].…”
Section: Discussionsupporting
confidence: 54%
“…These proposed regulations have the potential to substantially alter the Brazilian food supply as well as consumers' understanding, perceptions, purchase intentions, and intake of UPF. A recent randomized controlled trial in Brazil found that the exposure to FoP warning labels that only identify unhealthy foods helped consumers understand the unhealthiness of UPF and reduced their intentions to purchase this food [8], consistent with a growing body of literature that shows that warning labels improve consumers' ability to assess the healthfulness of products [10,11] and help them make healthier choices [12][13][14][15]. Conversely, nutrition and health claims have been shown to make consumers think a product is healthier than it actually is, working as a marketing strategy rather than an information tool (i.e., the "health halo" effect) [16,17].…”
Section: Introductionmentioning
confidence: 58%
“…Several studies have highlighted consumers' difficulty in understanding the percentages displayed on the GDA label [8,19,46]. When the labelling displays descriptors or color-coding, it gives the consumer the means to interpret numeric information and reduce processing time required to interpret labels [19].…”
Section: Discussionmentioning
confidence: 99%
“…An increasingly large number of studies evaluating FOP nutrition labels' impact on awareness [13,14], acceptability [15], understanding [14,16,17], use [13], or effects in healthfulness perceptions [18,19], have been conducted among Latin American populations. However, limited literature exists evaluating FOP label effects on consumer purchasing intentions (e.g.…”
Section: Abstract: Nutritional Labeling Latin-america Shopping Timementioning
confidence: 99%
“…For example, in the Mexican National Health and Nutrition Survey Survey of 2016, only 41% declared they use the labelling . Also, there is evidence that other types of labels could be more effective …”
Section: Discussionmentioning
confidence: 99%